2004
DOI: 10.1590/s0004-28032004000200014
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida em pacientes portadores de doença inflamatória intestinal: tradução para o português e validação do questionário "Inflammatory Bowel Disease Questionnaire" (IBDQ)

Abstract: Portuguese version of Inflammatory Bowel Disease Questionnaire is a valid and reproducible instrument which can be used to evaluate the quality of life of Brazilian inflammatory bowel diseases patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2
21

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 17 publications
3
22
2
21
Order By: Relevance
“…Se notó también prevalencia del sexo femenino, color pardo, casados/unión estable y escolaridad Enseñanza Secundaria completa. Esos datos, en especial el sexo, es evidente en la mayoría de los estudios internacionales y brasileños (8)(9)(10)(11)(12) . Mientras tanto, autores afirman que esa no sea característica general, pudiendo sufrir variaciones geográficas de localidades de la investigación, así como diferencias de hábitos culturales relacionados al género y los diferentes factores de riesgos que están inherentes (13) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Se notó también prevalencia del sexo femenino, color pardo, casados/unión estable y escolaridad Enseñanza Secundaria completa. Esos datos, en especial el sexo, es evidente en la mayoría de los estudios internacionales y brasileños (8)(9)(10)(11)(12) . Mientras tanto, autores afirman que esa no sea característica general, pudiendo sufrir variaciones geográficas de localidades de la investigación, así como diferencias de hábitos culturales relacionados al género y los diferentes factores de riesgos que están inherentes (13) .…”
Section: Discussionunclassified
“…Formado por 32 preguntas divididas en ámbitos, las cuales son presentadas de manera desordenada para disminuir la tendencia en las respuestas (8) .…”
Section: Materials Y Métodounclassified
See 1 more Smart Citation
“…Score 1 means the worst state of QL and 7 the best. Both SF-36 (15) and IBDQ (3) have already been translated and validated in Brazil. To determine the disease activity, we have used Lichtiger (16) for IUC and the Crohn's Disease Activity Index (CDAI) (17) , for CD.…”
Section: Methodsmentioning
confidence: 99%
“…It has incidence worldwide and represents a serious health problem, it affects young people, the course presents frequent recurrence, and there are highly severe clinical forms (1)(2) . This disease leads to important outcomes in patients' quality of life (QL) (3) . Several epidemiological studies have demonstrated a growing incidence of CD and IUC in the last decades (4)(5) .…”
Section: Introductionmentioning
confidence: 99%